Tourism Governance and Attainment of the Sustainable Development Goals in Africa. Issue 4 (3rd July 2020) - Siakwah, Pius; Musavengane, Regis; Leonard, Llewellyn
ABSTRACT: Inclusiveness that improves tourism governance is significant for development if benefits from tourism are distributed equitably. Declaration of 2017 as the International Year of Sustainable Tourism and adoption of the Sustainable Development Goals (SDGs) have seemingly brought tourism to the forefront of development even where the SDGs have limited tourism focus. This paper examines how tourism governance is poorly applied in Africa. It interrogates the challenges of integrating tourism governance, mining, and conservation within the SDGs framework in Africa. Sustainable tourism governance frameworks have not comprehensively inculcated trust, justice, social capital, power, and participation. Using mining and conservation in South Africa and Zimbabwe respectively, it analyses how mining affects sustainability, as actors in tourism are unable to conserve and protect tourism sites. Achieving the SDGs requires collaboration between international actors, governments, the private sector, and locals in an inclusive governance based on justice, inclusion trust and equitable power relations. Highlights Improvement in tourism governance is important for development Challenges of integrating tourism in the SDGs in Africa Tourism governance is however poorly applied in Africa Sustainable tourism governance neglects trust, justice, power and participation. Mining and poor conservation undermines sustainable tourism To achieve the SDGs, collaboration among varied actors is critical